Laparoscopic adenomectomy in BPH – Does it have a role today? - Ramalingam Manickam; Sivasankaran Nachimuthu; Senthil Kallappan; Mizar G. Pai (Asian Journal of Urology)
Symptomatic benign prostatic hyperplasia (BPH) is managed medically worldwide, but transurethral resection of prostate (TURP) is the gold standard in refractory cases. Holmium laser enucleation of prostate (HoLEP), laser vaporization are other options which are widely practiced. However in larger glands which are more than 80 g, open adenomectomy is still practiced. Laparoscopic adenomectomy is a minimally invasive option in such circumstances. This article explains about different techniques in minimally invasive adenomectomy and the role for this procedure today. Laparoscopic simple prostatectomy (LSP) has a place in symptomatic, larger prostatic adenoma in the hands of experienced laparoscopic surgeons when open simple prostatectomy is needed.